Computing Legal Analysis: A Guided Approach to Problem Solving in Contract Law - Marton Ribary; Antony Starza-Allen (Legal Education Review)
The paper proposes a guided methodology for problem solving in a first-year undergraduate contract law module. Developed from our teaching practice and inspired by theories of computational modelling, our approach helps students to identify and extract legal information from primary and secondary sources, and to organise what they have learned into structured frameworks. The method creates scaffolding for learning and a framework through which legal issues can be identified. These frameworks can be used to locate legal information relevant to the construction of analysis and argument to the point of producing legal advice with confidence. The paper describes our approach in five distinct stages: (1) extracting doctrinal content from legal sources, (2) organising such content into a coherent framework, (3) applying the framework to problem scenarios, (4) constructing , and (5) writing up detailed, authoritative, and persuasive legal advice.. Our methodology embeds essential skills aided by a “semantic web” of concepts from which one could draw inferences, and uses computer-inspired visualisation for constructing arguments. Computational thinking allows students to visualise connections between the initial categorisation of legal information and the constitutive elements of a persuasive legal argument to articulate and demystify the process of producing legal advice.